Tetraspanin CD81 regulates HSV-1 infection - Benayas, Beatriz (Med Microbiol Immunol, 2020)
Different members of the tetraspanin superfamily have been described to regulate different virus infectious cycles at several stages: viral entry, viral replication or virion exit or infectivity. In addition, tetraspanin CD81 regulates HIV reverse transcription through its association with the dNTP hydrolase SAMHD1. Here we aimed at analysing the role of CD81 in Herpes simplex virus 1 infectivity using a neuroblastoma cell model. For this purpose, we generated a CD81 KO cell line using the CRISPR/Cas9 technology. Despite being CD81 a plasma membrane protein, CD81 KO cells showed no defects in viral entry nor in the expression of early protein markers. In contrast, glycoprotein B and C, which require viral DNA replication for their expression, were significantly reduced in CD81 KO infected cells. Indeed, HSV-1 DNA replication and the formation of new infectious particles were severely compromised in CD81 KO cells. We could not detect significant changes in SAMHD1 total expression levels, but a relocalization into endosomal structures was observed in CD81 KO cells. In summary, CD81 KO cells showed impaired viral DNA replication and produced greatly diminished viral titers.